(untitled) - Liker, Jeffrey K. (New York, 2004)
In factories around the world, Toyota consistently makes the highest-quality cars with the fewest defects of any competing manufacturer, while using fewer man-hours, less on-hand inventory, and half the floor space of its competitors. The Toyota Way is the first book for a general audience that explains the management principles and business philosophy behind Toyota's worldwide reputation for quality and reliability.
Keywords: Industrial management,Quản trị công nghiệp